Effect of Surface Coatings on the Shelf Life and Quality of Kinnow Fruits During Storage - Mahajan, B V C; Dhillon , W S; Kumar , Mahesh (Journal of Postharvest Technology, 2013)
The Kinnow mandarin (Citrus nobilis x Citrus deliciosa) fruits of uniform size, disease and bruise free were picked randomly from all the four directions of the plants with the help of secateur. The fruits were sorted and washed with chlorine solution (100 ppm). Thereafter, the fruits were coated with ‘Nipro Fresh SS 40T and SS 50’ formulations. The fruits were air dried and packed in corrugated fibre board boxes (10 Kg capacity). The coated and control (uncoated) fruits were stored under cold storage conditions (5-7°C and 80-85% RH) and under ambient conditions (11-19°C and 80-85% RH). The various physico-chemical attributes of fruits were recorded in 30, 45 and 60 days in cold stored fruits and at 5, 10 and 15 days in fruits stored at ambient conditions. The results of the study indicated that Kinnow fruits coated with ‘Nipro Fresh SS 40T or SS 50’ showed significant delay in the change of weight loss, firmness, TSS, titratable acidity and vitamin-C content of Kinnow fruits. The present study envisaged that Kinnow fruit wax coated with these formulations can be successfully stored for 45 days under cold storage conditions (5-7oC and 90-95% RH) and for 10 days under ambient conditions (11-19oC and 65-70% RH) with highly acceptable sensory quality. The uncoated fruits, on the other hand, maintained postharvest shelf life of 30 days in cold storage and 5 days at ambient conditions.